A Rare Case Report of Cor triatriatum with Atrial Septal Defect Diagnosed at an Adult Age - Mamun, Mohammad Al; Thapa, Sanjog; Ataullah, Mohammad; Saha, Debbroto; Ghosh, Nitay Kumar; Kadir, ANM Monowarul; Sultana, Fouzia; Fatema, Nilufar (University Heart Journal, 2025)
Cor triatriatum dexter is a rare congenital heart defect divides the right atrium into two chambers with a varied clinical presentation ranging from asymptomatic to right heart failure. Accurate diagnosis is imperative as it may affect clinical decision making. This is a case of cor triatriatum dexter in a 53-year-old woman with Atrial septal defect with moderate tricuspid regurgitation which was diagnosed by Transthorasic Echocardiography (TTE) and later confirmed by Trans-esophageal Echocardiography (TEE). University Heart Journal 2024; 20(1): 40-43